Alternatives to the Central Bank in the Developing World - Collyns, Charles (Occasional Papers; Occasional Paper ;, 1983)
This paper discusses the operations of a wide range of central banking institutions in developing countries. The considerable diversity of economic, financial, and political conditions within the Third World has brought forth a wide variety of central banking institutions. Four polar types have been identified as providing coherent alternatives to the central bank. Historical experience certainly indicates that legislation on its own may not be enough to guarantee prudent behavior. Although many countries' central banking institutions have not yet come close to violating foreign exchange cover requirements or restrictions on government lending, in other cases the rules have simply been sidestepped by technical adjustments, altered expediently, or merely ignored. The organizational structure established by legislation probably plays a more positive part in determining a central banking institution's characteristic behavior. Operating procedures, channels of communication, and lines of command all exert some influence on where and how decisions are made in practice. The balance of power between government and monetary authority does not only depend on personality and outside support but will also be influenced by the institutional framework in which their interaction is established.